Pembuatan dan Instalasi Pengujian Turbin Screw dengan Variasi Debit Aliran - Habibie, Zhafran; Sumarjo, Jojo; Setiawan , Reza (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Screw type water turbine is one type of water turbine that has the potential to generate electricity on a small scale that is environmentally friendly, where this screw type water turbine is very suitable for rivers and irrigation flows in the territory of Indonesia. In this study, data analysis is aimed at the characteristics of the output power of the Archimedes screw turbine against the opening of the stopcock valve and testing is carried out on the modeling of this Pikohydro power plant including measuring water discharge, generator rotation, voltage, current, torque and generator output power and efficiency. In the process of making and testing screw-type water turbines, the addition of a water reservoir frame and a Weir V-Nocth discharge measuring device that measures the height of the discharge and the height of the turbine head tested. This study took place to determine the performance of screw turbines by testing variations in water discharge, by testing the Stopkran opening with 3 variations, namely ½ (38 mm wide), ¾ (50 mm wide), 1 (76 mm wide) with each producing water discharge 0.0045 m3 / s, 0.0065 m3 / s, 0.0078 m3 / s. The turbine tilt angle used is 30º and the turbine head is 0.9 m. The process of testing the tool is carried out in the open and the presence of PLN electric current, the goal is to make it easier to fill the water reservoir using a dip pump. After testing and calculating the data, the maximum result of shaft rotation is 1470 rpm with an output power of 53.7 watts at a discharge of 0.0078 m3/s. and maximum torque produced was 4.428 Nm at a discharge of 0.0045 m3/s and the maximum turbine efficiency of 0.078% at a discharge of 0.0078 m3/s.